Implications and challenges of using driver-based budgeting in contemporary business environment - Nikodijević Marija (Trendovi u Poslovanju)
The main characteristics of the business conditions of today's companies are frequent and intensive changes. The dynamic business environment of modern companies requires a new way of management that involves an implementation of new management models, methods, techniques and instruments that are adapted to the modern environment and able to respond to challenges and solve problems that arise in new business conditions. The aim of the paper is to describe the specifics of driver-based budgeting, as one of new management instruments. In comparison with traditional budgeting, driver-based budgeting possesses multiple advantages for companies that enable responding to changes in business environment in a more agile way. These advantages, as well as some perceived difficulties with its implementation in companies are described in the paper. The results of the paper contribute to the further development of the theory and can be an incentive for future research, as well as basis for making recommendations and practical instructions that could help companies improve their budgeting system.